Practices of non-relative child care givers in selected preschools in Quezon City - Sison, Joanne Tabora; Roldan, Aurorita Tan.,adviser (2009.)
The study examined the relationship between care giver practices and children's cognitive, physical, self-help, socio-emotional development as well as identified care giver characteristics such as: age, monthly income, job satisfaction, work experience and training. Reasons behind care giver practices and indigenous practices were also investigated. A total of 90 female care givers of children 3 to 5 years old were randomly selected to participate in the interview survey from 6 selected preschools in Quezon City. Majority of the participants are single and high school graduates. They have a mean age of 27 years, earn an average of P3,500 per month and have an average of four years of work experience as a child care giver. Of the 90 respondents, 50% previously attended at least one hour of care giver-related training while the other half has not receive any training. The study used Pearson-R to determine the relationship between care giver practices and their characteristics and T-test for independent means to determine the differences between the practices of the two groups - with and without training-- of respondents. Overall findings indicated that age is associated with practices related to children's physical and socio-emotional practices while monthly income and years of work experience were associated with practices related to children's cognitive,physical and socio-emotional development. Furthermore, there were statistical differences between care givers with and without training and their practices related to children's cognitive, physical and socio-emotional development. Those who have had a child-related training were more likely to engage in intellectually stimulating, physically encouraging and nurturing care giving practices compared to those without training. However, practices related to children's self-help development were not found to be associated with any of the characteristics studied. Moreover, job satisfaction was also not associated with any of the practices under study. Finally, care givers were influenced by the child's characteristicand temperament, parental instructions and preferences as well as their own personality and work load in their decision to engage in a particular activity with the child.
Thesis (Master of Family Life and Child Development)--University of the Philippines Diliman.
Keywords: Caregivers -- Philippines -- Quezon City; Child rearing -- Philippines -- Quezon City